ENTREPRENEURIAL MOTIVATION FOR STUDENTS MAJORING IN PUBLISHING AT POLIMEDIA BASED ON SOFT SKILLS - Carissa Dwilanisusantya; Purnomo Ananto (Jurnal Ilmiah Publipreneur, 2022)
This research is a causal associative research with a quantitative approach that aims to determine the entrepreneurship motivation of students in the Soft Skills-based publishing department. The type of data used in this study is qualitative descriptive research data. Sources of data for this study were obtained directly from filling out the questionnaire. The research population was all students of the Publishing Department of the Creative Media State Polytechnic and the sample of this study were third and fifth semester students who had received Entrepreneurship lessons as many as 134 people who were selected by probability sampling technique. The data analysis method used is simple linear regression. The results of this study indicate that soft skills play a very important role in the motivation of students of the Creative Media Publication Department in Jakarta. Recommendations are aimed at students who are expected to be able to apply indicators of improving social skills as an important factor in increasing motivation for entrepreneurship, especially in the type of goods/services entrepreneurship.